2021
DOI: 10.1016/j.jaut.2021.102703
|View full text |Cite
|
Sign up to set email alerts
|

Durable antibody response one year after hospitalization for COVID-19: A longitudinal cohort study

Abstract: Objectives Durability of the humoral immune response to SARS-CoV-2 has yet to be defined. We longitudinally evaluated during a 12-month period the antibody responses to SARS-CoV-2, and analysed predictors of antibody titres decline and seroreversion. Methods Prospective study conducted in a cohort of patients hospitalized for microbiologically-confirmed COVID-19. Blood and nasopharyngeal samples were sequentially obtained during hospital stay and at 1, 2, 6 and 12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
19
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 14 publications
16
19
1
Order By: Relevance
“…In this study, we assessed longitudinally the humoral immune response in individuals after infection with or vaccination against SARS-CoV-2. Our data show that S-IgG is found in levels distinctly higher than the positive threshold in almost all participants about seven weeks after infection, followed by a steady decline over months consistent with studies released over the past year [17][18][19]. Even after more than one year, the majority of convalesced patients remained S-IgG seropositive, indicating a more stable and long-lasting antibody response than evidence from the earlier stages of the pandemic might have suggested [20,21].…”
Section: Discussionsupporting
confidence: 75%
“…In this study, we assessed longitudinally the humoral immune response in individuals after infection with or vaccination against SARS-CoV-2. Our data show that S-IgG is found in levels distinctly higher than the positive threshold in almost all participants about seven weeks after infection, followed by a steady decline over months consistent with studies released over the past year [17][18][19]. Even after more than one year, the majority of convalesced patients remained S-IgG seropositive, indicating a more stable and long-lasting antibody response than evidence from the earlier stages of the pandemic might have suggested [20,21].…”
Section: Discussionsupporting
confidence: 75%
“…In our 8-month follow-up, we also reported that 76% of the patients still had detectable Neutralizing Antibodies (NAb) (1). Many studies reported short-term follow-up observations of less than 6 months (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), whereas others reported longitudinal observations, typically spanning less than 12 months post symptom onset (1,4,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Some studies reported contraction of anti-COVID humoral responses with a stronger initial decline (1,4,(23)(24)(25)27).…”
Section: Introductionmentioning
confidence: 70%
“…An important aspect of monitoring humoral responses has been having access to plasma from the same patients over 14 months. Most reports were based on cross-sectional analysis spanning less than 6 months (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) or up to 12 months (1,4,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Depending on the patient cohort, several studies reported a stronger initial contraction (1,4,(23)(24)(25)27) of anti-COVID humoral responses.…”
Section: Discussionmentioning
confidence: 99%
“…Data from convalescent patients showed that neutralizing antibody levels decline over time, between one to four months after symptom onset [ 16 ]. Moreover, the duration of the humoral immune response to SARS-CoV-2 among non-vaccinated convalescent patients, analyzed for twelve months, showed that the anti-spike IgG decline was positively associated with peak antibody titre and age, and inversely associated with WHO severity score [ 17 ].…”
Section: Introductionmentioning
confidence: 99%